Parallels in chapters of femicide and forced disappearances of women and girls in Ciudad Juárez and Ecatepec between 2008 and 2014: Patriarchy as a power system that guarantees impunity and misinformation [Paralelismos en los capítulos de feminicidios y desapariciones forzosas de mujeres y niñas en Ciudad Juárez y Ecatepec entre 2008 y 2014: el patriarcado como sistema de poder garante de la impunidad y la desinformación] (2016)
This paper develops a comparative analysis of different types of violence against women and girls in two Mexican municipalities: Ciudad Juarez (Chihuahua) and Ecatepec (State of Mexico). Although geographically far apart, both have disturbing similarities in relation to cases of forced teenage female disappearances and femicides, between 2008 and 2014. Through this research we delve into the misinformation regarding the cases studied and we analyze the official responses and actions implemented, or lack thereof, in order to clarify the facts. To do this, we have developed a work of historical context from a gender perspective and we have provided data and unpublished statements that have enriched the rigor and scientific quality of our study of this phenomenon.